Dynamic stall at high Reynolds numbers induced by ramp-type pitching motions. (10th May 2022) - Kiefer, Janik; Brunner, Claudia E.; Hansen, Martin O.L.; Hultmark, Marcus
Abstract: Abstract : The transient pressure field around a moderately thick airfoil is studied as it undergoes ramp-type pitching motions at high Reynolds numbers and low Mach numbers. A unique set of laboratory experiments were performed in a high-pressure wind tunnel to investigate dynamic stall at chord Reynolds numbers in the range of $0.5× 10^6≤ Re _c≤ 5.5× 10^6$ in the absence of compressibility effects. In addition to variations of mean angle and amplitude, pitching manoeuvres at reduced frequencies in the range of $0.01≤ k≤ 0.40$ were studied by means of surface-pressure measurements. Independently of the parameter variations, all test cases exhibit a nearly identical stall behaviour characterized by a gradual trailing-edge stall, in which the dynamic stall vortex forms approximately at mid-chord. The location of the pitching window with respect to the Reynolds-number-dependent static stall angle is found to define the temporal development of the stall process. The time until stall onset is characterized by a power law, where a small excess of the static stall angle results in a drastically prolonged stall delay. The reduced frequency exhibits a decrease in impact on the stall development in the case of angle-limited pitching manoeuvres. Beyond a critical reduced frequency, both load magnitudes and vortex evolution become reduced frequency independent and instead depend on the geometry of the motion and the convective time scale, respectively. Overall, the characteristics of vortex evolution induced by dynamic stall show remarkable similarities to the framework of optimal vortex formation reported in Gharib et al. ( J. Fluid Mech., vol. 360, 1998, pp. 121–140). The data from this study are publicly available at https://doi.org/10.34770/b3vq-sw14 .